The Authority Enhancement of The Election Supervisory Agency Post The Enforcement of Law Number 7 of 2017 Regarding General Election - Dwi Zaen Prasetyo (Constitutionale, 2022)
The implementation of elections in Indonesia has its own characteristics, where the regulation of the implementation of these simultaneous elections is set to be one in Law No. 7 of 2017 on General Elections. In addition, this Act also gives the Electoral Observer quasi-judicial authority in the process of dealing with administrative and arbitrary violations of the Electoral Process, with sanctions granted through an Electoral Observer Decision. It attracted the authors to research the electoral supervisory authorities experiencing enlargement and loading and to see the implications of quasi-judicial authority granted through several case analyses. This study aims to analyze the issues following (a) the form of authority enhancement given to Bawaslu and (b) the implementation of Bawaslu's authority in its effort to handle election violations and resolve election disputes in Lampung Province according to Law No. 7 Year 2017 regarding the General Election. The method used in this research is a normative-empirical law study. Data sources of this research are primary, secondary and tertiary law objects using qualitative analysis methods. The result obtained from this research shows enhancement of the election supervisor's authority in the areas of: First, handling process of criminal election violation; Second, the handling of election organizers' ethical code violation; Third, the handling of election administration violation; Fourth, election dispute settlement mechanism. The enhancement of Bawaslu's authority process is a characteristic that is a given quasi-judicial in handling administrative violations and election process disputes that can be seen in 4 (four) election regimes.